Reproductive Health Issues and Use of Family Planning Methods among Married Adolescent Mothers - Nepal, Samata; Aryal, Shreyashi (Journal of Lumbini Medical College, 2020)
Introduction: Adolescent pregnancy is a major public health concern in low- and middle-income countries. Nepal ranks among the twenty countries with the highest child marriage rates in the world. Adolescent mothers are at higher risk for poorer maternal and neonatal outcomes. This study intended to find the reproductive health issues and use of family planning methods among married adolescent mothers at a tertiary care center in a western part of Nepal. Methods: This was a cross-sectional study conducted among adolescent mothers who attended the family planning counselling session at Community Medicine Out-patient Department at a tertiary care center. Pre-tested semi-structured questionnaire was used for data collection and variables were entered in SPSSTM version 16. Descriptive statistics were presented in terms of mean and percentage. Results: Among 235 adolescent mothers, the mean age of adolescent mothers was 18.02 years (SD = 1.13). Almost 93.2% had not used any kind of contraceptive methods previously. Limited knowledge, uncomfortable talking about contraception and spousal denial were common reasons for not using contraception. Obstetric related complications were observed in 13.6% and one in ten neonates required neonatal intensive care unit admission during the study period. After the counselling session, six out of ten expressed current choice of long acting reversible contraceptives method in which Jadelle implant was preferred. Conclusion: Our study among the adolescent mothers showed that use of family planning methods before pregnancy had been very low. Policies need to focus on meeting the unmet need for family planning among married adolescent girls.